A Case for Team-Based Learning as an Effective Collaborative Learning Methodology in Higher Education. Issue 2 (7th September 2020) - Vlachopoulos, Panos; Jan, Shazia K; Buckton, Rodney
Abstract: This paper reports the results from the implementation of Team-Based Learning (TBL) methodology at a large Australian university. The study found a significant difference between students' learning experience and hours spent studying pre and post TBL. The study also found a significant positive relationship between in-built TBL assessments and finals grades pointing to the capacity of TBL to predict performance. Findings of the study present valuable practical implications for academics looking to implement carefully structured collaborative learning methodologies that effectively enhance student engagement, experience and learning along with fostering teamwork and communication skills.